Massive spin-3/2 models in D=2+1 - E.L. MendonÃ§a; A.L.R. dos Santos; D.S. Lima (Physics Letters B, 2017)
We have demonstrated that the fermionic part of the so called âNew Topologically Massive Supergravityâ, which is of third order in derivatives, is classically equivalent to self-dual models of lower order in derivatives, forming then a sequence of self-dual descriptions SD(i), with i=1,2,3 meaning the order in derivatives of each description. We have connected all the models by symmetry arguments through a Noether Gauge Embedment approach. This is completely equivalent to what happens in the bosonic cases of spins 1, 2 and 3, so some discussion about the similarities is made along the work. An analogue version of the FierzâPauli theory is suggested. Then through the NGE approach a fourth order model is obtained, which in our point of view would be the analogue version of the linearized New Massive Gravity theory for spin-3/2 fermionic particles.